FEATURES OF THE INTERACTION OF THE INDIVIDUAL AND SOCIETY IN THE ERA OF GLOBALIZATION: UKRAINIAN CONTEXT - Чорноморденко, І. В.; Карпінський, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the issues of relationships and interactions "human – person" and "human – society" in the era of globalization. Attention is accented on the offered V.I. Vernadskiy methods of their decision.